2012
DOI: 10.1073/pnas.1120985109
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-specific activation of tyrosine kinase networks during prostate cancer progression

Abstract: Dominant mutations or DNA amplification of tyrosine kinases are rare among the oncogenic alterations implicated in prostate cancer. We demonstrate that castration-resistant prostate cancer (CRPC) in men exhibits increased tyrosine phosphorylation, raising the question of whether enhanced tyrosine kinase activity is observed in prostate cancer in the absence of specific tyrosine kinase mutation or DNA amplification. We generated a mouse model of prostate cancer progression using commonly perturbed non-tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
151
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 59 publications
5
151
0
Order By: Relevance
“…Recent studies have demonstrated that the progression of CRPC and the development of resistance to current treatments were associated with an increased activity of tyrosine kinase signaling. 45 However, contrary to other cancer types, somatic mutations or amplification of tyrosine kinase genes have rarely been identified in CRPC patients. 45 The lack of mutation also suggests that tumors are not addicted to a dominant signaling pathway, and likely to promote intertumoral and intratumoral heterogeneity in their response to a specific inhibitor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the progression of CRPC and the development of resistance to current treatments were associated with an increased activity of tyrosine kinase signaling. 45 However, contrary to other cancer types, somatic mutations or amplification of tyrosine kinase genes have rarely been identified in CRPC patients. 45 The lack of mutation also suggests that tumors are not addicted to a dominant signaling pathway, and likely to promote intertumoral and intratumoral heterogeneity in their response to a specific inhibitor.…”
mentioning
confidence: 99%
“…45 However, contrary to other cancer types, somatic mutations or amplification of tyrosine kinase genes have rarely been identified in CRPC patients. 45 The lack of mutation also suggests that tumors are not addicted to a dominant signaling pathway, and likely to promote intertumoral and intratumoral heterogeneity in their response to a specific inhibitor. In recent years, the progress in the understanding of the essential role played by RTKs in prostate cancer development has led to the assessment of various TKIs in clinical trials (for review, see Ojemuyiwa et al 46 ).…”
mentioning
confidence: 99%
“…However, the cost and time of crossbreeding, as well as matching strain genetic background, can provide significant obstacles. By double infection with different single-gene viral stocks or preparation of a single polycistronic lentiviral vector, various combinations of genetic events can be easily introduced and quickly assessed in the epithelial cells of interest (Xin et al 2006;Cai et al 2011a;Drake et al 2012). Using this efficient strategy, we showed that high levels of ERG protein collaborate with activation of the PI3K/AKT pathway or enhanced AR signaling, resulting in the progression of PIN lesions to frank prostate adenocarcinoma (Zong et al 2009) (Fig.…”
Section: Strengths and Weaknesses Of The Tissue Recombination/transplmentioning
confidence: 99%
“…Patients with mCRPC have a poor prognosis and have an expected survival of approximately 18-20 months. 12,13 Several mechanisms are believed to lead to CRPC development: 1) persistence of intratumoural androgens due to in situ steroidogenesis 14 or biosynthesis from adrenal glands and testes; 15 2) wild-type androgen receptor (AR) amplification and/or protein overexpression; 16,17 3) constitutive activation of AR signaling and/or AR-targeted transcription due to AR mutation 18 or post-translational modification; 19 4) activation of other ligand-bound receptors, including receptor tyrosine kinases, 20 and their downstream pro-survival signaling pathways; and 5) the presence of prostate cancer Contemporary agents in the management of metastatic castration-resistant prostate cancer REVIEW This review is CUA-accredited for Section 3 credits of the MOC Program of the RCPSC. Got to www.cuaj.ca for details.…”
Section: Introductionmentioning
confidence: 99%